THE CONTEXTS OF THE STUDENT TAKING THE MICRO TEACHING CLASS - Julie, Hongki (International Journal of Indonesian Education and Teaching (IJIET), 2017)
In this paper, the researcher would only present the results obtained by the researcher related to the context of students. To find out the context of the students who took this course, the researcher did the taking: (1) find the studentsâ€™ hometown data and the studentsâ€™ GPA from the Sanata Dharma Academic Information System (SDAIS), and (2) make a questionnaire consisting of four questions filled by students at the first meeting. The results of this research was as follows: (1) ten students came from Java Island and nine students came from outside Java Island, (2) six students had GPA above 3.00 and thirteen students had GPA below 3.00, (3) eleven students said that their vocation was to be a teacher when they first chose this program, (4) there were 13 students who experience change of vocation, and (5) there were eighteen students who stated that their obstacles in taking this lecture were â€œI had not "settled" with myself,â€ while one other student said that â€œmastering teaching materials was my obstacle in taking this lecture.â€Â DOI: https://doi.org/10.24071/ijiet.2017.010206